Role of infection in the middle lobe syndrome in asthma. Issue 5 (May 1992) - Springer, C; Avital, A; Noviski, N; Maayan, C; Ariel, I; Mogel, P; Godfrey, S
Abstract : Twenty one children with asthma aged 1.0-10.5 years (mean (SD) 3.3 (2.5) years) were admitted to the hospital to evaluate pulmonary right middle lobe or lingular collapse lasting one to 12 months (mean (SD) 4.4 (3.8) months). Seven children had mild asthma and were treated with inhaled beta 2 agonists as needed. Nine had moderate asthma treated with either sodium cromoglycate or slow release theophylline. Five had severe asthma treated with inhaled steroids. Each child underwent fibreoptic bronchoscopy under local anaesthesia and a bronchoalveolar lavage. Differential cell counts of the lavage fluid revealed predominance of neutrophils in 12 patients (57%). In nine of these patients cultures grew pathogenic bacteria, mainly Haemophilus influenzae and Streptococcus pneumoniae. There was no correlation between the severity of asthma and a positive bacterial culture. There was also no correlation between the duration of the right middle lobe collapse and a positive culture. We conclude that longstanding right middle lobe collapse in asthmatic children is often associated with bacterial infection.